2019
DOI: 10.1021/acs.iecr.8b04081
|View full text |Cite
|
Sign up to set email alerts
|

Improved Vine Copula-Based Dependence Description for Multivariate Process Monitoring Based on Ensemble Learning

Abstract: This paper proposes a boosting vine copula-based dependence description (BVCDD) method for multivariate and multimode process monitoring. The BVCDD aims to improve the standard vine copula-based dependence description (VCDD) method by establishing an ensemble of submodels from sample directions based on a boosting strategy. The generalized Bayesian inference-based probability (GBIP) index is introduced to assess the degrees of a VCDD model (submodel) to depict different samples, which means how likely an obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
(92 reference statements)
0
16
0
Order By: Relevance
“…To conceptually validate the superiority and effectiveness of the proposed MBCCA-based distributed process monitoring approach over its counterparts, comparisons with MBPCA-, DPCA-, and DICA-based methods are implemented with application to the Tennessee Eastman (TE) process. …”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To conceptually validate the superiority and effectiveness of the proposed MBCCA-based distributed process monitoring approach over its counterparts, comparisons with MBPCA-, DPCA-, and DICA-based methods are implemented with application to the Tennessee Eastman (TE) process. …”
Section: Case Studiesmentioning
confidence: 99%
“…The TE process has become a well-known benchmark platform for validating different data-driven process monitoring methods because of its relatively complicated configuration. The flowchart of the TE benchmark process is depicted in Supporting Information Figure S1, which consists of multiple units: a reactor, a condenser, a vapor–liquid separator, a recycle compressor, a stripper, and a plant-wide control system .…”
Section: Case Studiesmentioning
confidence: 99%
“…To detect process faults, a generalized Bayesian inference probability (GBIP) index had been used to monitor the process status. To improve the quality of VCDD, Zhou et al proposed boosting VCDD by establishing an ensemble of sub-models from sample directions based on a boosting strategy and combined the VCDD method and active learning strategy to solve the problem of missing samples . To enhance the robustness of the VCDD method, a copula double-subspace (CDS) including margin distribution subspace (MDS) and dependence structure subspace (DSS) was proposed .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that a new drug optimization method based on the nanopore force spectroscopy has been proposed. By all-atom molecular dynamics simulations, the binding strength between a drug molecule and a target protein could be electrically detected. , Ensemble learning is a method that integrates multiple machine learning algorithms by using some rules, so as to achieve better effects than a single machine learning algorithm . There are two kinds of ensemble learning; one is boosting, and another is bagging.…”
mentioning
confidence: 99%
“…30,31 Ensemble learning is a method that integrates multiple machine learning algorithms by using some rules, so as to achieve better effects than a single machine learning algorithm. 32 There are two kinds of ensemble learning; one is boosting, and another is bagging. The former's characteristic is the dependencies between weak learners, while for the latter, there are no dependencies between weak learners; all weak learners could be parallel fitted.…”
mentioning
confidence: 99%